Block Ciphers with Matrices Operating Alternately over Columns and Rows - Freyre, Pablo; Cuellar, Oristela; Díaz, Nelson; Alfonso, Adrián (Journal of Science and Technology on Information security, 2021)
Abstract—In this paper, we present the dynamic cryptographic algorithms for long states named ACDEL-2D and ACDEL-3D. The first one was inspired by Rijndael and the second one was inspired by 3D, a three-dimensional block cipher. In both proposals, MDS matrices are used alternately on rows and columns of the state and all transformations used in the encryption process are randomly selected depending on pseudorandom sequences. In the block cipher ACDEL-3D the state takes the form of a rectangular parallelepiped or cuboid. Tóm tắt—Trong bài báo này, chúng tôi trình bày các thuật toán mật mã động cho các trạng thái dài, có tên là ACDEL-2D và ACDEL-3D. Thuật toán đầu tiên bắt nguồn từ thuật toán Rijndael và thuật toán thứ hai bắt nguồn từ thuật toán 3D, một thuật toán với khối dữ liệu được biểu diễn ở dạng ba chiều. Cả hai đề xuất đều sử dụng xen kẽ ma trận MDS trong các hàng và cột của trạng thái và tất cả các phép biến đổi được sử dụng trong quá trình mã hóa được chọn ngẫu nhiên tùy thuộc vào chuỗi giả ngẫu nhiên. Trong mật mã khối ACDEL-3D, trạng thái có dạng hình chữ nhật song song hoặc hình khối.